2015
DOI: 10.1002/mrc.4291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ascorbic acid (vitamin C) on the ESR spectra of the red and black hair: pheomelanin free radicals are not always present in red hair

Abstract: Increased incidence of melanoma in the population with red hair is conditioned by synthesis of pheomelanin pigments in the skin and their phototoxic properties. The recent research has shown that free radicals of pheomelanin are produced not only by the influence of UV irradiation, but also in UV-independent pathways of oxidative stress. It has been ascertained, that the color of the hair is not always determinant of the amount of pheolemanin radicals in red hair. Therefore, in order to evaluate the risk of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The ESR spectra of the sample were measured before and after irradiation. The irradiation was conducted by a xenon lamp at an extensity of 300 W, and the samples were placed at a certain distance to avoid heating. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESR spectra of the sample were measured before and after irradiation. The irradiation was conducted by a xenon lamp at an extensity of 300 W, and the samples were placed at a certain distance to avoid heating. , …”
Section: Methodsmentioning
confidence: 99%
“…The irradiation was conducted by a xenon lamp at an extensity of 300 W, and the samples were placed at a certain distance to avoid heating. 35,36…”
Section: Antiphotoaging Activity Testmentioning
confidence: 99%
“…Nevertheless, the various environmental conditions such as light, moisture, metal ions, heat, and base can cause denaturation and decomposition of physicochemical properties in ASA. Mg-Al LDH as an antacid and anti-pepsin agent is quite biocompatible, so it can be used as a good reservoir to protect ASA against decomposition ( 26 27 28 29 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of social technology and the improvement of free radical research technology, it has been found that the production mechanism of exercisable endogenous free radicals also includes neutrophil mechanism, prostaglandin mechanism, and calcium mechanism [1]. The mitochondrial mechanism and xanthine oxidase mechanism are generally considered two mechanisms for the production of sportive endogenous free radicals [2]. Modern medical planners are more inclined to believe that free radicals are the cause of many diseases in the body and that acute intense exercise produces a large number of free radicals [3].…”
Section: Introductionmentioning
confidence: 99%